Recommendations on the utilization of the in vitro, in situ and enzymatic methods for the study of feed digestion - González, D.; Ruíz, M.E.; Romero, F.; Pezo, Danilo A. (Inter-American Institute for Cooperation on Agriculture, 1992)
Summarizes the recommendations on the utilization of the in vitro, in situ and enzymatic methods, w. partic. ref. to in vitro digestion; enzymatic degradation; in situ digestibility; and mathematical models.